Transforming Sharia Economic Dispute Resolution through E-Court for Simple, Fast, and Affordable Justice - Asyiqin, Istianah Zainal; Fitriyanti, Fadia; Susila, M. Endriyo; Akbar, M. Fabian; Wirayudha, Dimas Putra (Prophetic Law Review, 2025)
This study critically examines the implementation of the electronic court (e-Court) system in resolving Sharia economic disputes within Indonesia’s Religious Courts, focusing on selected jurisdictions in Jakarta, Yogyakarta, Central Java, and East Java. Introduced through Supreme Court Regulations No. 1 of 2019 and No. 7 of 2022, the e-Court system aims to modernize judicial processes and realize justice that is simple, fast, and affordable. Using a qualitative descriptive approach, the research draws on data from eight Religious Courts: East Jakarta, South Jakarta, Sleman, Wonosari, Sidoarjo, Surabaya, Pemalang, and Slawi, through interviews, observation, and document analysis. Findings show that while the e-Court system enhances administrative efficiency and transparency, its implementation remains uneven. Urban courts such as Jakarta and Surabaya demonstrate successful digital integration, whereas Wonosari, Pemalang, and Slawi face obstacles in infrastructure, internet access, and digital literacy. These disparities create hybrid practices and raise concerns about procedural validity and data security. From a prophetic law perspective, the e-Court reform embodies the moral ideals of humanization (amar ma’ruf), liberation (nahi munkar), and transcendence (tu’minuna billah). However, unequal access to digital justice contradicts these prophetic values. The study concludes that achieving ethical and inclusive digital transformation requires embedding prophetic legal principles into judicial policy to ensure that modernization serves humanity and justice, not merely administrative efficiency.